Active tuberculosis and multiple sclerosis: the importance of screening before treatment - Amorim, Leizian de Souza; Zaidan, Paloma Peter Travassos; Menezes, Felipe Toscano Lins de; Oliveira, Enedina Maria Lobato de (Arquivos de Neuro-Psiquiatria, 2025)
Tuberculosis (TB), a chronic infection caused by the Mycobacterium tuberculosis complex, has an increased risk of reactivation in conditions that affect the immune system, such as MS, and its treatment with disease-modifying drugs (DMDs). The present is a retrospective study of 2,036 patients diagnosed with MS followed at the Department of Neurology and Neurosurgery of Escola Paulista de Medicina, Universidade Federal de São Paulo, from February 1994 to September 2023. Of that total, 6 were included in this case series, taking different DMDs: fingolimod (n = 2), interferon beta 1a (n = 2), glatiramer acetate (n = 1) and cyclophosphamide (n = 1). In our study, two patients experienced worsening disability during tuberculosis treatment, while three others had increased disability after completing treatment. We reinforce the importance of screening all patients eligible for DMD treatment, especially the highly effective modern ones, and the importance of developing research-based guidelines for screening infectious diseases among patients with MS.
Keywords: Multiple Sclerosis; Tuberculosis; Risk Assessment